The Philosophy in the Motives of Classical Hand-Drawn Madurese Batik - Ong Mia Farao Karsono; Lintu Tulistyantoro (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
The aim of this paper is to uncover of the philosophy contained in the main motive and the background motive of Madurese classical hand-drawn batik. This paper use qualitative descriptive method, in which the researchers act as reseach instrument by interviewing batik craftsmen, which include Pamekasan batik, Tanjung Bumi batik, Sumenep batik and Sampang batik. Data analysis is performed by inspecting the motives from batik photographs displayed in their galleries, and relating it to the result of the interviews and written theories. Findings and discussions reveal that the main classical batik motives of “sabet rante” and “bamboo” contain the moral philosophy about the tradition of proposing to the bride and of living courageously. While the beras tompa (spilled-rice) and panji susi (swastika) background motives in Madurese batik contain the philosophy about thrifty and balanced living. Keywords: Madurese batik, philosophy,hand-drawn,classical